2020
DOI: 10.2147/ijn.s239550
|View full text |Cite
|
Sign up to set email alerts
|

<p>Magnesium-doped Nanostructured Titanium Surface Modulates Macrophage-mediated Inflammatory Response for Ameliorative Osseointegration</p>

Abstract: Background: Next generation of coating materials on the surface of implants is designed with a paradigm shift from an inert material to an osteoimmunomodulatory material. Regulating immune response to biomedical implants through influencing the polarization of macrophage has been proven to be an effective strategy. Methods: Through anodization and hydrothermal treatment, magnesium ion incorporated TiO 2 nanotube array (MgN) coating was fabricated on the surface of titanium and it is hypothesized that it has os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Mg 2+ as the bioactive elements has been widely used to enhance the attachment and differentiation of osteoblastic cells, as well as accelerating vascularization and mineralization to enhance bone regeneration [ 62 ]. Additionally, Mg 2+ can promote the polarization of macrophages from M1 to M2 phenotype and reduce the inflammation in the repair area, which is another important mechanism to promote bone repair [ 63 ]. Therefore, for the SA-GG/TMP6040 group, the slowly released Mg 2+ from the TMP-BG was positive to accelerate the regeneration of subchondral bone ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mg 2+ as the bioactive elements has been widely used to enhance the attachment and differentiation of osteoblastic cells, as well as accelerating vascularization and mineralization to enhance bone regeneration [ 62 ]. Additionally, Mg 2+ can promote the polarization of macrophages from M1 to M2 phenotype and reduce the inflammation in the repair area, which is another important mechanism to promote bone repair [ 63 ]. Therefore, for the SA-GG/TMP6040 group, the slowly released Mg 2+ from the TMP-BG was positive to accelerate the regeneration of subchondral bone ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study indicated that calcium phosphate nanoparticles deposited in TiO2 nanotube could enhanced the adhesion and proliferation of human gingival epithelial cells (HGECs) and human gingival broblasts (HGFs) which means nanostructured titanium surfaces were bene cial to the mucosal barrier [58]. Besides, TiO 2 nanotubes can modulate macrophage immune response [59]. Host immune responses and in ammatory state may also in uence the complex host-bio lm interaction and therefore in uence the composition of the colonizing microbiota and their expressed functions [48,60].…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro results suggested that the MAO-650 surface did not only support the proliferation and differentiation processes of the bone-forming cells but also elicited a favorable osteoimmunomodulatory effect by inhibiting the inflammatory activity of macrophages. In another study, Qiao et al [ 261 ] deposited an Mg-incorporated NT array (MgN) coating on the surface of Ti and the in vitro and in vivo results showed that the newly developed coating may have endowed the surface with immunomodulating features by eliciting an inhibitory effect on the inflammatory response of macrophages. Unlike random roughness, various microfabrication methods have been employed to obtain patterns with a desired shape and size on the biomaterial surface [ 173 ].…”
Section: Development Of Bone Biomaterials With Immunomodulatory Prmentioning
confidence: 99%
“…Since the infiltration of oxygen and nutrients may determine the fate and polarization of macrophages, the porosity and pore size of the biomaterial have been acknowledged as another relevant surface characteristic [ 182 , 261 ]. Smaller pores could disrupt the nutrients and oxygen diffusion, especially in the center of the implantable device, thus resulting in a local hypoxic microenvironment [ 178 ].…”
Section: Development Of Bone Biomaterials With Immunomodulatory Prmentioning
confidence: 99%